Three new free-living marine nematode species of the family Comesomatidae from Mangrove wetlands in Jinmen County, Taiwan - Xiao, Yueping; Guo, Yuqing (Zootaxa, 2023)
Three new free-living marine nematodes, belonging to the genera Dorylaimopsis, Comesoma and Paracomesoma are described from the mangrove wetlands of western Taiwan Island. Dorylaimopsis jinmendaoica sp. nov. is characterized by having a cuticle with lateral differentiation of longitudinal rows of two rows of larger dots in the middle of the body, a spiral amphideal fovea with 2.5–2.75 turns, excretory pore anterior to nerve ring and 17–21 fibriform precloacal supplements. Comesoma quattuordecimsupplementata sp. nov. is characterized by having a spiral amphideal fovea with 2.5–2.75 turns and 14 fibriform precloacal supplements. Paracomesoma paralissum sp. nov. is characterized by having a spiral amphideal fovea with 3.0 turns and 40 fibriform precloacal supplements. Differentiating characteristics of all known male Dorylaimopsis, Comesoma and Paracomesoma species are also given.